Pattern Foster Person Old in Formation Character Religion of Early Childhood in Subdistrict Bay Meranti Pelalawan District Riau - Izzah, Nurul; Maryatun, Ika Budi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research uses a qualitative approach with a survey method. This research was conducted in Teluk Meranti Subdistrict, Pelalawan Regency Riau, the data source of this research was determined by purposive sampling technique consisting of parents who have children aged 4-6 years. Data were collected by interview through a questionnaire. The data that has been obtained is analyzed using Miles & Huberman (1992) including data reduction, data presentation, and conclusion drawing. The analyzed data were then tested for validity using triagulation techniques. The results of this study shows three findings (1) there are three types of parenting patterns applied by parents in Teluk Meranti Subdistrict, Pelalawan Regency Riau, namely 70% democratic parenting patterns seen in the provisions of rules that do n't burden children, giving advice and directions to children, and good communication in the family, Then authoritarian parenting 20% where parents tend to give physical punishment, few communications rooms, and permissive parenting 10% parents give freedom without parental supervision of children . (2) Religious characters result from democratic parenting are praying, fasting, familiarizing the words please, sorry, and thank you you, darling greetings, darling the creed, helping each other, keeping the environment clean and loving living things.